Steel pipe a guide for design and installation. (American Water Works Association, 2004)
Discusses the fundamentals and applications of statistical thermodynamics for beginning graduate students. Features a step-by-step development of the subject with each chapter carefully written to address student difficulties in learning this challenging subject. Both example and prompted homework problems are included.
Keywords: Water-pipes -- Design and construction -- Handbooks, manuals, etc.; Pipe, Steel -- Design and construction -- Handbooks, manuals, etc.; elektronické knihy; electronic books